Two novel mutations in the fibrinogen γ nodule - Kotlín, Roman; Pastva, Ondřej; Stikarová, Jana; Hlaváčková, Alžběta; Suttnar, Jiří; Chrastinová, Leona; Riedel, Tomáš; Salaj, Peter; Dyr, Jan E (Thrombosis research, 2014)
INTRODUCTION: Congenital dysfibrinogenemia and hypofibrinogenemia are rare diseases characterized by inherited abnormality in the fibrinogen molecule, resulting in functional defects (dysfibrinogenemia) or low fibrinogen plasma levels (hypofibrinogenemia). MATERIALS AND METHODS: We have described two abnormal fibrinogens - fibrinogen Hranice (γ Phe204Val) and Praha IV (γ Ser313Gly). The carrier of the Hranice mutation was a 40-year-old female with low fibrinogen levels. The carrier of the Praha IV mutation was a 42-year-old man with a history of idiopathic thrombosis, low functional fibrinogen levels, and a prolonged thrombin time. RESULTS: Fibrin polymerization kinetics measurement was normal in both cases (after the addition of either thrombin or reptilase), as well as was fibrinolysis. Scanning electron microscopy and confocal microscopy revealed significantly wider fibers in both cases, when compared with fibers prepared from healthy control samples. Although both cases are situated in the γ-nodule, they manifested differently. While the γ Ser313Gly mutation manifested as dysfibrinogenemia with a thrombotic background, the γ Phe204Val mutation manifested as hypofibrinogenemia without clinical symptoms. The mutation sites of both fibrinogens are in highly conserved regions of the fibrinogen γ chains. γ Ser313 is situated in a class 16:18 β hairpin and is involved in hydrogen bonding with γ Asp320. γ Phe204 is situated in an inverse γ turn and may be involved in π-π interactions. CONCLUSIONS: Both mutations cause conformational changes in fibrinogen, which lead either to impaired fibrinogen assembly (fibrinogen Hranice) or abnormal fibrinogen function (fibrinogen Praha IV).
Keywords: Humans; Hereditary coagulation disorders; Fibrinogens, Abnormal; fibrinogeny abnormální; Female; Coagulation; dospělí; lidé; Thrombosis; fibrinogen; Afibrinogenemia; Adult; ženské pohlaví; Abnormal fibrinogens; bodová mutace; Male; Fibrinolysis; afibrinogenemie; Point Mutation; fibrinolýza; Fibrinogen; mužské pohlaví; Fibrin; fibrin